Ethylene Antagonizes Salt-Induced Growth Retardation and Cell Death Process via Transcriptional Controlling of Ethylene-, BAG- and Senescence-Associated Genes in Arabidopsis - Pan, Ya-Jie; Liu, Ling; Lin, Ying-Chao; Zu, Yuan-Gang; Li, Lei-Peng; Tang, Zhong-Hua (Frontiers in Plant Science, 2016)
The existing question whether ethylene is involved in the modulation of salt-induced cell death to mediate plant salt tolerance is important for understanding the salt tolerance mechanisms. Here, we employed Arabidopsis plants to study the possible role of ethylene in salt-induced growth inhibition and programmed cell death (PCD) profiles. The root length, DNA ladder and cell death indicated by Evan’s blue detection were measured by compared to the control or salt-stressed seedlings. Secondly, the protoplasts isolated from plant leaves and dyed with Annexin V-FITC were subjected to flow cytometric (FCM) assay. Our results showed that ethylene works effectively in seedling protoplasts, antagonizing salt-included root retardation and restraining cell death both in seedlings or protoplasts. Due to salinity, the entire or partial insensitivity of ethylene signaling resulted in an elevated levels of cell death in ein2-5 and ein3-1 plants and the event were amended in ctr1-1 plants after salt treatment. The subsequent experiment with exogenous ACC further corroborated that ethylene could modulate salt-induced PCD process actively. Plant Bcl-2-associated athanogene (BAG) family genes are recently identified to play an extensive role in plant PCD processes ranging from growth, development to stress responses and even cell death. Our result showed that salinity alone significantly suppressed the transcripts of BAG6, BAG7 and addition of ACC in the saline solution could obviously re-activate BAG6 and BAG7 expressions, which might play a key role to inhibit the salt-induced cell death. In summary, our research implies that ethylene and salinity antagonistically control BAG family-, ethylene-, and senescence-related genes to alleviate the salt-induced cell death.